Early Life Stress in Depressive Patients: HPA Axis Response to GR and MR Agonist - Baes, Cristiane W.; Martins, Camila M.; Tofoli, Sandra M.; Juruena, Mario F. (Frontiers in Psychiatry, 2014)
Background: Evidence indicates that early life stress (ELS) can induce persistent changes in the HPA axis to respond to stress in the adult life, lead to depression. These appear to be related to the impaired of HPA hormones through binding to glucocorticoid (GR) and mineralocorticoid receptors (MR). The aim of this study was to evaluate the impact of ELS in HPA axis response to challenges with GR and MR agonists in depressed patients. Methods: We included 30 subjects, 20 patients with current major depression (HAM-D21 ≥17). Patients were recruited into two groups according to ELS history assessed by the Childhood Trauma Questionnaire (CTQ). The cortisol measures in the saliva and plasma were evaluated after using (at 10:00pm) placebo, fludrocortisone (MR agonist) or dexamethasone (GR agonist). Results: Depressed patients showed a significantly lower salivary cortisol upon waking after placebo compared with controls. Moreover, cortisol awakening responses (CAR) after MR agonist were found to be lower in depressed patients than in controls. With CTQ scores, HAM-D21, BMI and CAR after placebo, GR agonist, MR agonist we found in a Linear Regression model that depressive patients with ELS (p=0.028) show differences between Placebo vs MR agonist (R= 0.51; p< 0.05) but not after GR agonist; in depressive patients without ELS the data show differences between Placebo vs MR agonist (R= 0.69; p< 0.05);but now as well Placebo vs. GR agonist (R= 0.53; p< 0.05). Conclusion: Our findings indicate that MR activity is impaired in depressed patients compared with controls. Furthermore, in spite of the previous limitations described, in depressed patients with ELS, there was suppression by MR agonist, indicating that patients with ELS are sensitive to MR agonists. In contrast with depressed patients without ELS, where we find suppression after both MR and GR agonist. These data suggested that in ELS an imbalance between MR/GR with MR dysfunction.